Applications of iridium-catalyzed asymmetric allylic substitution reactions in target-oriented synthesis - Qu, Jianping; Helmchen, Günter (Accounts of chemical research, 2017)
Metal catalyzed allylic substitution is a cornerstone of organometallic and synthetic chemistry. Enantioselective versions have been developed with catalysts derived from transition metals, most notably molybdenum, nickel, ruthenium, rhodium, iridium, palladium, and copper. The palladium- and the iridium-catalyzed versions have turned out to be particularly versatile in organic synthesis because of the very broad scope of the nucleophile and great functional group compatibility. Assets of the iridium-catalyzed reaction are the formation of branched, chiral products from simple monosubstituted allylic substrates, high degrees of regio- and enantioselectivity, and use of modular, readily available chiral ligands. The possibility to use carbon, nitrogen, oxygen, and sulfur compounds as well as fluoride as nucleophiles allows a wide range of chiral building blocks to be prepared.Our Account begins with the presentation of fundamental reaction schemes and chiral ligands. We will focus our discussion on reactions promoted by phosphoramidite ligands, though numerous chiral ligands have been employed. The subsequent section presents a brief overview of reaction mechanism and experimental conditions. Two versions of the iridium-catalyzed allylic substitution have emerged. In type 1 reactions (introduced in 1997), linear allylic esters are commonly used as substrates under basic reaction conditions. In type 2 reactions (introduced in 2007), environmentally friendly branched allylic alcohols can be reacted under acidic conditions; occasionally, derivatives of allylic alcohols have also been applied. A unique feature of the type 2 reactions is that highly electrophilic allylic intermediates can be brought to reaction with weakly activated alkenes.The subsequent text is ordered according to the strategies followed to transform allylic substitution products to desired targets, most of which are natural products or drugs. Syntheses starting with an intermolecular allylic substitution are discussed first. Some fairly complex targets, for example, the potent nitric oxide inhibitor (−)-nyasol and the drug (−)-protrifenbute, have been synthesized via less than five steps from simple starting materials.Most targets discussed are cyclic compounds. Intermolecular allylic substitution with subsequent ring closing metathesis is a powerful strategy for their synthesis. Highlights are stereodivergent syntheses of Δ9-tetrahydrocannabinols (THC), wherein iridium- and organocatalysis are combined (dual catalysis). The combination of allylic alkylation with a Diels-Alder reaction was utilized to synthesize the ketide apiosporic acid and the drug fesoterodine (Toviaz). Sequential allylic amination, hydroboration and Suzuki-Miyaura coupling generates enones suitable for conjugate addition reactions; this strategy was employed in syntheses of a variety of alkaloids, for example, the poison frog alkaloid (+)-cis-195A (pumiliotoxin C).Intramolecular substitutions offer interesting possibilities to build up stereochemical complexity via short synthetic routes. For example, in diastereoselective cyclizations of chiral compounds, substrate control can be overruled by catalyst control in order to generate cis- and trans-isomers selectively from a given precursor. This approach was used to prepare a variety of piperidine and pyrrolidine alkaloids. Finally, complex polycyclic structures, including the structurally unusual indolosesquiterpenoid mycoleptodiscin A, have been generated diastereo- and enantioselectively from olefins by polyene cyclizations and from electron-rich arenes, such as indoles, in dearomatization reactions.